2021
DOI: 10.1016/j.ultsonch.2021.105840
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-excited hydrogen radical from NiFe layered double hydroxide for preparation of ultrafine supported Ru nanocatalysts in hydrogen storage of N-ethylcarbazole

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…S15d and e †), the Ru 3p and Ru 3d peaks are shifted to lower bonding energy, indicating that the oxidative Ru species are mainly reduced into Ru 0 throughout the HER process. 57 Consequently, it is believed that metallic Ru is the primarily active sites for HER. (The surface and in situ embedded nanoneedle arrays Ru-NiCo 2 O 4 with an appropriate amount and highly-dispersed Ru nanoparticles can serve as the primary HER active site.)…”
Section: Evaluation Of Electrocatalytic Her Performancementioning
confidence: 99%
“…S15d and e †), the Ru 3p and Ru 3d peaks are shifted to lower bonding energy, indicating that the oxidative Ru species are mainly reduced into Ru 0 throughout the HER process. 57 Consequently, it is believed that metallic Ru is the primarily active sites for HER. (The surface and in situ embedded nanoneedle arrays Ru-NiCo 2 O 4 with an appropriate amount and highly-dispersed Ru nanoparticles can serve as the primary HER active site.)…”
Section: Evaluation Of Electrocatalytic Her Performancementioning
confidence: 99%
“…The collapse of cavitation bubbles will produce high temperature, high pressure and so on of special physical and chemical changes, which provides favorable conditions for the rapid synthesis of nanomaterials with uniform particle size distributions. Liu [43] prepared RuNPs loaded on NiFe-LDHs by ultrasonic-assisted reduction, showing excellent catalytic activity in NEC hydrogenation. The surface hydroxyl groups of the carrier were excited into •H under ultrasound to reduce Ru 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that when using the ultrasound-assisted reduction method to prepare Ru-based catalysts supported on LDH, if the ultrasonic power is too low or the ultrasonic time is too short, the generated energy is not enough to excite the —OH groups on the surface of LDH to produce enough •H, resulting in incomplete reduction of Ru 3+ . However, too high ultrasonic power and too long ultrasonic time can easily cause Ru NPs to agglomerate, leading to a decrease in the number of exposed active sites [36] . Therefore, the selection of ultrasonic preparation conditions is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…This extraordinary high-energy environment provides a special platform for the growth of novel nanostructures [33] , [34] . Our previous study found that under ultrasonic conditions, the hydroxyl groups on the surface of LDH were excited to generate highly reducing hydrogen radicals (•H), which successfully reduced the supported noble metal cations [35] , [36] . Compared with the traditional chemical reduction method, this method does not require the addition of chemical reducing agents and stabilizers, and the obtained metal nanoparticles are smaller and highly dispersed.…”
Section: Introductionmentioning
confidence: 99%